Novosti in klinična obravnava neonatalne nekonjugirane hiperbilirubinemije - Bratanič, Borut (Medicinski razgledi, 2004)
Neonatal unconjugated hyperbilirubinemia continues to be one of the most frequent and puzzling problems in neonatology. Ten years ago, the guidelines for management of neonatal unconjugated hyperbilirubinemia were changed when the decision levels for therapeutic interventions were elevated. This year, the American Academy of Pediatrics reviewed and updated its guidelines for management of neonatal unconjugated hyperbilrubinemia. This review article describes advances in the field of neonatal unconjugated hyperbilirubinemia. Among diagnostic procedures, measurements of exhaled CO, "free" bilirubin, transcutaneous bilirubin, screening test for evoked auditory brainstem potentials and brain imaging are highlighted. Investigation of bilirubin's neurotoxicity goes on with research on inhibition of protein/peptide phosphorylation, impaired homeostasis of intracellular calcium, effects of bifirubin on cell membranes and apoptosis, and on the role of P-glycoprotein in protection of the brain against bilirubin. Recent advances in therapy are described, including improvement of light sources for phototherapy using lightemitting diodes, and the use of inhibitors of hem oxygenase, bilirubin reductase, photonic analogues, miniature reactors of glucuronosyl transpherase, as well as gene therapy for the Cligler Najjar type 1 genetic syndrome. In the last part of the article, new guidelines for clinical management of jaundiced new-borns are summarised, with special emphasis on new-borns in whom serum bilirubin reaches level of 427 micromol/1. The appendix contains a new decision tree for clinical management of jaundiced new-borns.
Keywords: Hiperbilirubinemija; Jaundice, Neonatal; Kernikterus; Hyperbilirubinemia; Diagnosis; Zlatenica novorojenčka; Therapy; Novorojenček; novorojenčki; Kernicterus; Infant, Newborn; zlatenica; zdravljenje; diagnostika